Structural and morphological changes of breast cancer cells induced by iron(ii) complexes. Issue 7 (3rd February 2022) - Nel, Janske; Siniscalco, David; Hognon, Cécilia; Bouché, Mathilde; Touche, Nadége; Brunner, Émilie; Gros, Philippe C.; Monari, Antonio; Grandemange, Stéphanie; Francius, Grégory
Abstract : Iron(ii )-based complexes were able to penetrate into the cytoplasm without disrupting the cell membrane. The complexes induced size, morphological, stiffness and cytoarchitectural changes in both triple negative breast cancer and normal cells. Abstract : Metal-based complexes are well-established cancer chemotherapeutic drug candidates. Although our knowledge regarding their exact activity vs. toxicity profile is incomplete, changes in cell membrane biophysical properties and cytoskeletal structures have been implicated as part of the mechanism of action. Thus, in this work, we characterised the effects of iron(ii )-based complexes on the structural and morphological properties of epithelial non-tumorigenic (MCF 10A) and tumorigenic (MDA-MB-231) breast cell lines using atomic force microscopy (AFM), flow cytometry and immunofluorescence microscopy. At 24 h of exposure, both the MCF 10A and MDA-MB-231 cells experienced a cell softening, and an increase in size followed by a re-stiffening at 96 h. In addition, the triple negative breast cancer cell line, MDA-MB-231, sustained a notable cytoskeletal and mitochondrial reorganization with increased actin stress fibers and cell-to-cell communication structures. An extensive all-atom molecular dynamic simulation suggests a possible direct and unassisted internalization of the metallodrug candidate, and confirmed that the cellular effects could not be ascribed to the simple physical interaction of the iron-based complexes with the biological membrane. These observations provide an insight into a link between the mechanisms of action of such iron-based complexes as anti-cancer treatment and cytoskeletal architecture.